Smart Façades: Declination with the Electrochromic Glass - G. Loddo (Challenging Glass Conference, 2016)
Energy saving and environmental protection don’t represent only a technical problem but also, and maybe most of all, an ethical problem. From this point of view, the Mediterranean area, characterized by a considerable Sunshine for at least 8 months a year, is configured as particularly suitable for the use of all building systems that can reach the objectives provided by the latest global climate conferences. The architectural heritage of the Mediterranean area is various both in typological terms and in relation to building materials used. If you want to find materials and components common to the area certainly the windows, and exacting the glazing linked to them, represent a very significant element that can considerably contribute to energy savings. Our group is concerned, since 2009, to test the behaviour, in the energy field, of electrochromic glass. The phases of the studies, presented at many conferences, have already demonstrated efficiency in terms of savings that can be achieved by envelopes integrated with the EC. The testing, conducted on full scale models, was divided into three steps temporally sequential. We built two identical test rooms each other for exposure, size (4x4x2.70 m) and of the envelope composition. Traditional low-emission panels were put in place in the first room, the EC glass were placed in the second one. Measuring tools were positioned in the test rooms, to detect the most important internal thermo physical parameters. This study is divided in three steps, according to a façade configuration with glass surfaces gradually increasing. The research compares internal conditions, detected during the three phases, and it clarifies the relationships between façade configuration and both inside and outside circumstances.